Insight review of attached microalgae growth focusing on support material packed in photobioreactor for sustainable biodiesel production and wastewater bioremediation. (December 2020) - Rosli, Siti Suhailah; Amalina Kadir, Wan Nadiah; Wong, Chung Yiin; Han, Fon Yee; Lim, Jun Wei; Lam, Man Kee; Yusup, Suzana; Kiatkittipong, Worapon; Kiatkittipong, Kunlanan; Usman, Anwar
Abstract: The suspended microalgal cultivation systems targeting the production of lipid for biodiesel is still unable to meet the commercial and economic feasibility due to high energy and cost inputs during the harvesting process. Currently, the attached microalgal cultivation systems are known as an innovative technology to resolve the problematic aspects of suspended cultivation as the biomass can be easily separated from the culture medium with negligible energy input and no chemical need. Accordingly, this paper is focusing on reviewing various support materials utilized by researchers in growing the attached microalgal biomass in either fixed bed or fluidized bed bioreactor to ensure sustainable biomass production prior for biodiesel. An extensive review of the cultivation conditions impacting the growth of attached microalgal biomass is conducted in determining the optimized condition to enhance biomass productivity. The novelty of this paper is presented through in-depth analyses and discussions concerning the kinetic models and mechanisms study in selecting the suitable support materials for attached microalgal growth system. The incorporation of the cultivation condition parameter in predicting the growth of attached microalgae biomass via kinetic study is crucial in proffering new directions for technological developments and microalgal industry application. The ability of attached microalgal biomass in efficiently assimilate the nutrients available in the nutrient-rich wastewater for the microalgae growth is considered as an economical feasible approached. The suitable photobioreactor designs for growing the attached microalgal biomass are also discussed in detail in ensuring the sustainability of attached microalgal biomass production. Graphical abstract: Image 1 Highlights: Attached cultivation to ease microalgal biomass harvest for biodiesel production. Microalgae cells attachment mechanism onto the support material. Kinetic model to predict the growth of attached microalgal biomass. Nutrient-rich wastewater treatment via assimilation by attached microalgal biomass. Type of photobioreactors to promote the growth of attached microalgal biomass.